1993
DOI: 10.1021/bi00086a016
|View full text |Cite
|
Sign up to set email alerts
|

Selection and characterization of a mutant T7 RNA polymerase that recognizes an expanded range of T7 promoter-like sequences

Abstract: The compatible plasmids pKGP1-1 and pCM-X# will confer chloramphenicol resistance to Escherichia coli harboring the two plasmids if the T7 RNA polymerase produced from pKGP1-1 can recognize the T7 promoter carried on pCM-X# and transcribe the CAT gene that is cloned behind the promoter [Ikeda et al. (1992) Biochemistry 31, 9073-9080]. When E. coli harbor pKGP1-1 and a pCM-X# plasmid that carries a point mutation in the T7 promoter that destroys promoter activity (an inactive pCM-X#), the T7 RNA polymerase will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Previous studies have demonstrated the ability to screen for functional mutant polymerases in E. coli (29,30). In this way, a mutant T7 RNAP was identified that directs transcription from several different promoter sequences that are not utilized by the wild-type enzyme (29). It would be difficult to use the same strategy to select for T7 RNAP variants that utilize an all-RNA promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the ability to screen for functional mutant polymerases in E. coli (29,30). In this way, a mutant T7 RNAP was identified that directs transcription from several different promoter sequences that are not utilized by the wild-type enzyme (29). It would be difficult to use the same strategy to select for T7 RNAP variants that utilize an all-RNA promoter.…”
Section: Discussionmentioning
confidence: 99%
“…T7 RNAP is highly specific for its promoter sequence (TAATACGACTCACTATA), and exhibits virtually no detectable activity on the consensus promoter of the related bacteriophage T3 ( A A T TA ACC CTCACTA A A, differences underlined) 21,22. Despite decades of study and several attempts to engineer the specificity of T7 RNAP towards other promoters22,23 including that of T3, a mutant T7 RNAP capable of recognizing the T3 promoter has not been previously reported.…”
mentioning
confidence: 99%
“…Thus, the result confi rms a central rule of directed evolution approaches: 'What you get is what you screen for' [62]. The DNA-dependent RNA polymerase of bacteriophage T7 is an ideal target for directed evolution studies because it is a single-subunit enzyme that has been extensively characterized by mutational [63][64][65][66][67][68][69] and structural studies [70][71][72][73]. Like other phage RNA polymerases, the enzyme is highly specifi c for its promoter.…”
Section: Tuning Polymerase Activity By Directed Evolutionmentioning
confidence: 99%